LINGUACULTURAL AND LEXIC-SEMANTIC FEATURE OF THE WORD FOOD IN CONTRAST UZBEK AND ENGLISH LANGUAGES: LINGUACULTURAL AND LEXIC-SEMANTIC FEATURE OF THE WORD FOOD IN CONTRAST UZBEK AND ENGLISH LANGUAGES - Sailaubaeva, Gozzal (Журнал иностранных языков и лингвистики, 2025)
In human life language is the most important communication tool in it. as a communication tool this interaction between fellow humans can be established properly (Fitrah, dkk, 2017). Every region inhabited by humans must have a language in it as a means of communication. The words we use to describe food go beyond mere labels; they encapsulate culinary traditions, agricultural practices, and the social fabric of a culture.